Reproductive tract infections in women seeking abortion in Vietnam - Thủy Đỗ; Kurtzhals Jørgen; Mỹ Hương Nguyễn; Rasch Vibeke (BMC, 2009)
Abstract Background Women requesting abortion are at increased risk of developing RTI complications. However, RTI control in many resource-poor countries including Vietnam have been faced with logistical and methodological problems due to lack of standardized definitions of RTIs, lack of well-validated diagnostic criteria, lack of accurate laboratory tests, and lack of diagnostic equipment and skills. This article investigates the prevalence of RTIs among Vietnamese abortion-seeking women, to evaluate the available diagnostic techniques, and to assess antibiotic resistance among aetiological agents of RTI. Method The study was conducted in Phu-San hospital (PSH) from December 2003 through April 2004 among 748 abortion clients. A structured questionnaire was used to collect data on socio-economic and reproductive characteristics. Specimens were collected for laboratory analyses of chlamydia, gonorrhoea, trichomoniasis, vaginal candidiasis (VC), bacterial vaginosis (BV) and syphilis. To assess the validity of the obtained results, the study was repeated among 100 women and the duplicate samples were analysed at PSH and Copenhagen University Hospital (CUH). Results In all 54% of the women were diagnosed as having an RTI, including 3.3% with sexually transmitted infections. Endogenous infections were most prevalent (VC 34% and BV 12%) followed by chlamydia (1.3%) and trichomoniasis (0.7%). The sensitivity of culture for VC and BV was 30% and 88%, respectively, when tests in PSH were measured against tests in CUH. Antibiotic resistance was common among bacterial isolates. Conclusion RTIs are common among women seeking abortion. The presence of RTIs is associated with an increased risk of developing iatrogenic infections, routine administration of prophylactic antibiotic to all women undergoing abortion should be considered. However, the choice of routine prophylactic antibiotics should be based on relevant surveillance data of antibiotic resistance. Moreover, since the accuracy of diagnosis is doubtful and to address the problem of under-diagnosed and treated RTIs new investment in diagnostic facilities with simple performed microscopy or improved rapid tests should also be taken into consideration.